Human ability to discriminate surface chemistry by touch. Issue 1 (11th December 2017) - Carpenter, Cody W.; Dhong, Charles; Root, Nicholas B.; Rodriquez, Daniel; Abdo, Emily E.; Skelil, Kyle; Alkhadra, Mohammad A.; Ramírez, Julian; Ramachandran, Vilayanur S.; Lipomi, Darren J.
Abstract : Human ability to discriminate between hydrophilic and hydrophobic surfaces is attributed to differences in vibrational frequencies generated while sliding at particular velocities and normal forces. Abstract : The sense of touch is mediated by the interaction of a soft material ( i.e., skin) with the texture and chemistry of an object's surface. Previous work designed to probe the limits of tactile perception has been limited to materials with surface asperities larger than the molecular scale; such materials may also have different bulk properties. We demonstrate in a series of psychophysical experiments that humans can discriminate surfaces that differ by only a single layer of molecules, and can "read" patterns of hydrophobicity in the form of characters in the ASCII alphabet. We design an apparatus that mimics free exploration of surfaces by humans and corroborate the experimental results with a theoretical model of friction that predicts the velocities and pressures that permit discrimination. These results demonstrate that forces produced, while sliding a finger along surfaces, interact with the mechanoreceptors of the skin to allow the brain to discriminate surfaces that differ only by surface chemistry. While we used intentionally simple surface modifications in this study (silanized vs. oxidized silicon), these experiments establish a precedent for using the techniques of materials chemistry in psychology. They also open the door for the use of more sophisticated, molecularly engineered, materials in the future.